2020
DOI: 10.5812/ijp.98117
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Pro-Oxidant-Antioxidant Balance in Physiologic and Pathologic Jaundice

Abstract: Background: Jaundice can be observed in two-thirds of infants. Bilirubin prevents damage to the DNA from the oxidative stress of reactive oxygen species (ROS). Moreover, bilirubin has anti-inflammatory and anti-apoptotic roles in addition to antioxidant properties. Objectives: We decided to compare pro-oxidant-antioxidant balance (PAB) in physiologic and pathologic jaundice. Methods: This cross-sectional study evaluated 171 infants more than 35 weeks of gestational and > 2 days of postnatal age who were admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[13] In another study, it was shown that a pathological increase in bilirubin levels irrespective of its neurotoxic properties can change the PAB in favor of antioxidants. [14] In asphyxia, it was demonstrated that PAB in combination with hypoxic-ischemic encephalopathy grade might have a better predictive value for the prognosis of asphyxiated babies and predicting future neurologic problems in asphyxiated term infants. [15] There are more data on other oxidative indexes in preterm and term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…[13] In another study, it was shown that a pathological increase in bilirubin levels irrespective of its neurotoxic properties can change the PAB in favor of antioxidants. [14] In asphyxia, it was demonstrated that PAB in combination with hypoxic-ischemic encephalopathy grade might have a better predictive value for the prognosis of asphyxiated babies and predicting future neurologic problems in asphyxiated term infants. [15] There are more data on other oxidative indexes in preterm and term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it was shown that there was no signi cant relationship between umbilical cord blood pro-oxidant antioxidant's balance and type of delivery [12]. In another study, it was shown that a pathological increase in bilirubin levels irrespective of its neurotoxic properties can change the PAB in favor of antioxidants [13]. In asphyxia, it was demonstrated that PAB in combination with hypoxic-ischemic encephalopathy (HIE) grade might have a better predictive value for the prognosis of asphyxiated babies and predicting future neurologic problems in asphyxiated term infants [14].…”
Section: Discussionmentioning
confidence: 99%